THE INFLUENCE OF EASE OF PAYMENT USING QRIS ON PURCHASING DECISIONS WITH BRAND TRUST AS A MODERATING VARIABLE - Elshifa, Aria; Avianita Rachmawati; Muhamad Azkia; Rahmat Aji Nuryakin; Clora Widya Brilliana (JURNAL ILMIAH EDUNOMIKA, 2025)
ABSTRACT This study is a quantitative study with an explanatory approach, namely an approach that uses a number of previous studies as the main reference in building assumptions and proving the formulated hypothesis, namely the variable Ease of Payment Using QRIS on Purchasing Decisions and the Brand Trust variable can moderate the influence of these variables. The data used in this study are primary data that researchers obtained from 500 students spread throughout Indonesia. The questionnaire distributed contains 5 statements, namely statements that strongly agree, statements that agree, statements that are normal or possible, statements that disagree, and statements that strongly disagree. The data collected was analyzed using the smart PLS 4.0 analysis tool. Keywords: Ease Of Payment Using Qris, Purchasing Decisions , Brand Trust